To Design a Framework for Enhancing Social Emotional Learning Competencies of Teachers - Kaur, Jasleen (My University, 2024)
For the past decade, an increasing number of researchers and educationalists have called for the need to focus on the social and emotional aspects of teachers’ professional development and student holistic development beyond academic mastery. Recent researches have concluded that the preschool years are a crucial developmental period wherein the development of Social-Emotional Learning (SEL) is a crucial milestone in the lives of preschool students. Regular exposure to SEL in classroom learning enhances social skills, emotional competence, teacher-student relationships, academic performance, and reduces impulsiveness in students. Preschool teachers play a requisite role and are considered the engine that powers SEL interventions and practices in preschools and classrooms. Therefore, teachers’ SEL understanding is essential, especially in the Early Childhood Care and Education (ECCE) profession. Understanding SEL can help preschool teachers recognize and manage their emotions and create and practice positive emotions (such as joy and enthusiasm) to stimulate SEL in themselves and their students. The current study is done in 2 phases. In phase 1 of the research, the current study examines the preschool teachers' understanding of SEL pre- and post-training. The study evaluates the effectiveness of 12-hour (4 sessions) teachers’ training on their understanding of SEL. The training module is developed to explain the concept of the five core competencies of SEL, including self-awareness, self-management, social awareness, relationship management, and responsible decision making as defined by CASEL. The study is based on the data collected from 100 teachers teaching in 19 preschools located in the Ludhiana and Patiala districts of Punjab in India. In phase 2 of the research, the study intends to propose and validate the SEL framework, titled "The ECCE Happiness Framework," designed to improve the emotional competence of preschool students. The designed framework constitutes three key happiness practices, including social engagement, sharing and caring, and mindfulness. The study examines the impact of the SEL framework on the emotional competence of 486 preschool students studying in the 19 preschools in Ludhiana and Patiala districts of Punjab in India. The Paired sample t-test was used in Statistical Package for Social Sciences (SPSS) to examine and compare the teachers’ understanding of SEL pre- and post-training. The results suggest that training interventions are very useful for improving teachers’ understanding of SEL. Further, Partial Least Square-Structural Equation Modeling (PLS-SEM) was used to measure the impact of the SEL framework on the emotional competence of preschool students. Based on teachers’ observations, the results were measured. The findings suggested that the ECCE Happiness Framework has improved the emotional competence of preschool students in Punjab. The study findings direct the Ministry of Education, academicians, and preschools in Punjab and India as a whole to develop and implement teaching philosophies, strategies, curriculums, training programs, and interventions that focus on promoting teachers’ SEL understanding and students' emotional competence in Punjab and India as a whole.
Keywords: Social Engagement; Sharing and Caring; Engaged students; Happiness; Preschoolers; Happy Schools